PERAKITAN PUPUK MAJEMUK N-ZEOLIT-P UNTUK PERBAIKAN SIFAT KIMIA INCEPTIC HAPLUDULT, SERAPAN NP DAN HASIL PADI GOGO AROMATIK - , Muhammad Rifan, Ir.,MP. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The Utilization of Inceptic Hapludult has the obstacle on low soil fertility constraints. Many alternative can be used for that soil improvement, i.e. use N-Zeolite-P fertilizer. The objectives of this research are to: enhance the cations adsorption of zeolite, study the effectiveness of Phosphate Rock (PR) acidulation with humic acids, get N-Zeolite-P fertilizer formulations with NP grade effective and efficient in the supply of N and P nutrients, study the effect and interaction composition, dosages of N-Zeolite-P fertilizer, and upland rice strains on chemical properties of soil, the distribution of N and P uptake by plants, the growth and yield of upland rice in Inceptic Hapludult. This study consisted of three stages, the first stage is the preparation, characterization, fertilizer ingredient testing, and assembly of N-Zeolite-P fertilizer